Whole‐Genome Sequencing of a Single Viral Species from a Highly Heterogeneous Sample. Issue 47 (28th August 2015) - Han, Hee‐Sun; Cantalupo, Paul G.; Rotem, Assaf; Cockrell, Shelley K.; Carbonnaux, Martial; Pipas, James M.; Weitz, David A.
Abstract: Metagenomic studies suggest that only a small fraction of the viruses that exist in nature have been identified and studied. Characterization of unknown viral genomes is hindered by the many genomes populating any virus sample. A new method is reported that integrates drop‐based microfluidics and computational analysis to enable the purification of any single viral species from a complex mixed virus sample and the retrieval of complete genome sequences. By using this platform, the genome sequence of a 5243 bp dsDNA virus that was spiked into wastewater was retrieved with greater than 96 % sequence coverage and more than 99.8 % sequence identity. This method holds great potential for virus discovery since it allows enrichment and sequencing of previously undescribed viruses as well as known viruses. Abstract : On a drop‐in basis : A new platform that integrates drop‐based microfluidics and computational analysis was developed for purification of a single viral species from a mixed sample and retrieval of its complete genome sequence. This method was used to retrieve the genome sequence of SV40 spiked into wastewater with more than 96 % sequence coverage and 99.8 % sequence identity. The platform can also be used to detect and identify unknown viruses.